INTERNALISASI NILAI-NILAI KEAGAMAAN LEWAT MEDIA - Najla, Armiah (UIN Antasari Banjarmasin, 2014)
The values of Islam in society are very important. Moreover, the highly complex challenges of our time. Internalization of Islamic values does not just rely on family or school environment. However, it should also involve the media. Because the media have been criticised as a factor in the destruction of the morality and ethics of society rather than enlightening the nation. The negative effects of accessing media are more dominant than the positive ones. Media managers should have the awareness to build and preserve the moral values of the nation. For that, the media is expected to have a formula in shaping and planting of Islamic values to the minds of the audience. The media should be able to transform itself into a form of locomotive movement in internalization of Islamic teachings, because the majority of media audiences are Muslims. Through Islamic media, it is expected to create social structures that have Islamic mindset and behavior in daily life